Effects of Mobile Health Technologies on Uptake of Routine Growth Monitoring among Caregivers of Children Aged 9 to 18 Months in Kenya - Edna Nyang'echi; Justus Osero (SAGE Publishing, 2021)
This study aimed at finding out the effects of mobile health ( m health) technologies on uptake of Routine Growth Monitoring (RGM) among caregivers of children aged above 9 months in Kenya. This was a quasi-experimental study. The experiment groups received Short Text Message (STM) and Voice Call (VC). The analysis demonstrates that in month 1, caregivers who received STM were 6.875 times more likely to take their children for RGM compared to control (OR = 6.875; 95 CI: 3.591-13.164); caregivers who received VC were 6.750 times more likely to take their children for RGM compared to those in control arm (OR = 6.750; 95 CI: 3.522-12.938). Policy makers and implementers in the health will find these study findings useful in deciding whether or not to adopt STM or VC in improving uptake of RGM for children above 9 months.